Electrostatic Coupling and Identification of Single-Defects in GaN/AlGaN Fin-MIS-HEMTs. (June 2019) - Grill, A.; Stampfer, B.; Im, Ki-Sik; Lee, J.-H.; Ostermaier, C.; Ceric, H.; Waltl, M.; Grasser, T.
Highlights: Charge trapping effects are considered as one of the most severe reliability issues in GaN/AlGaNMIS-HEMTs. Thus, the identification of the origin and the physical properties of active defects is one of the key factors to improve the stability of GaN technology. In this work, we suggest two neighboring nitrogen vacancies as the origin of correlated random telegraph noise (RTN) emissions in a GaN/AlGaN fin-MIS-HEMT. Electrostatic coupling between these two defects is calculated using three different approaches and the results are verified using a Hidden Markov Model (HMM). Abstract: Charge trapping effects are considered as one of the most severe reliability issues in gallium nitride (GaN)/aluminium gallium nitride (AlGaN) metal-insulator-semiconductor HEMTs (MISHEMTs). Thus, the identification of the origin and the physical properties of active defects is one of the key factors to improve the stability of GaN technology. In this work, we suggest two neighboring nitrogen vacancies as the origin of correlated random telegraph noise (RTN) emissions in a GaN/AlGaN fin-MISHEMT. We determine the magnitude of electrostatic coupling between these two defects by using three different approaches and verify the results by simulating the RTN emissions of a similar system using a Hidden Markov Model (HMM).